There and back again. Heidegger and Tolkien on technology (Tábano, 2020)
The purpose of this paper is to analyze Tolkien’s and Heidegger’s thoughts on technology with the aim of justifying that the metaphysical/ontological position of the second brings problems regarding the solution of the problem concerning technology that can be easily solved if one opts for a Tolkienian approach to the problem, that is, from a rather mundane or everyday dimension of humanity (or “hobbitry”, to be more precise).